Post-traumatic-stress in the context of childhood maltreatment: pathways from attachment through mentalizing during the transition to parenthood - Ensink, Karin; Bégin, Michaël; Martin-Gagnon, Gabriel; Biberdzic, Marko; Berthelot, Nicolas; Normandin, Lina; Fonagy, Peter; Bernazzani, Odette; Borelli, Jessica L. (Frontiers in Psychology, 2023)
This study aimed to clarify the role of mentalizing in pathways from attachment to Post Traumatic Stress Symptoms (PTSS) in survivors of childhood maltreatment (CM). We focused on the transition to parenting, a critical period for reworking parenting representations to reduce intergenerational maltreatment cycles. Study participants included 100 pregnant CM survivors. We assessed PTSS with the SCID and attachment and mentalizing with the Adult Attachment Interview (AAI), which was rated for Attachment and Reflective Functioning (RF). Regarding Re-experiencing trauma symptoms, the results of the path analysis were consistent with mediation. CM survivors' mentalizing about their early relationships with their parents (RF-Other) directly impacted Re-experiencing trauma symptoms, and attachment had an effect on Re-experiencing trauma symptoms through mentalizing (RF-Other). Regarding Arousal/Reactivity symptoms, the results of the pathways analysis were consistent with partial mediation by mentalizing about early relationships with parents (RF-Other). In addition to the pathway from attachment via mentalizing (RF-Other) to Arousal/Reactivity, the pathway between attachment and Arousal/Reactivity also remained significant. This study provides new evidence of a mentalizing and attachment model of PTSS in CM survivors. The findings indicate that increased mentalizing about early relationships with parents is an important process associated with lower PTSS. Finally, we discuss the implications of developing interventions for CM survivors to reduce PTSS. Scaffolding the development of mentalizing regarding attachment relationships in which CM occurred may help CM survivors reduce the intrusion of traumatic memories and decrease trauma-related arousal and reactivity symptoms. Interventions to help CM survivors mentalize regarding parents and attachment relationships in which trauma occurred may be particularly important during the transition to parenting when activation of representations of parenting can trigger PTSS.